The economic valuation of noise reduction projects: a cost-benefit analysis approach - Salva, Nuno Gonçalo Simões (2016)
The main purpose of this Work Project consists in performing a practical Cost-Benefit Analysis from a social perspective of two noise reduction projects in industrial sites that aim at complying with the existing regulation. By doing so, one may expect a more comprehensive view of the benefits and costs of both projects, as well as relevant insight to the way noise exposure regulation must be optimally defined in Portugal and within the EU area.